Will Islamic marketing survive in today’s world? - Jan, Muhammad Tahir; Wan, Hooi Lai (2018)
Purpose – This paper discusses various challenges that marketers need to resolve in implementing marketing practices that are consistent with the Islamic ethical framework. Design/ methodology/ approach - This paper develops a framework that describes three main issues/ challenges faced by Islamic Marketing in today’s world. These issues are extracted from the literature by thoroughly studying published work on the topic both in conventional and Islamic marketing contexts. Further, the extracted issues were then searched and matched with some real business cases with their implications. Findings – The three issues identified are related to ‘halal’, ‘legality’, and ‘branding’. For successful implementation of Islamic marketing and to capture the Islamic market, marketers will have to thoroughly address these three issues. Marketing non Islamic products simultaneously with Islamic products is unlikely to entice Muslim consumers to purchase such products in an Islamic market. Practical Implications – the paper provides valuable insights into the challenging task facing companies wishing to market their products in Muslim countries because of the variations in the differing social, political and cultural outlook.